2017
DOI: 10.3389/fpsyt.2017.00242
|View full text |Cite
|
Sign up to set email alerts
|

Mediators Linking Childhood Adversities and Trauma to Suicidality in Individuals at Risk for Psychosis

Abstract: Suicidality is highly prevalent in patients at clinical high risk (CHR) for psychosis. Childhood adversities and trauma are generally predictive of suicidality. However, the differential effects of adversity/trauma-domains and CHR-criteria, i.e., ultra-high risk and basic symptom criteria, on suicidality remain unclear. Furthermore, the underlying mechanisms and, thus, worthwhile targets for suicide-prevention are still poorly understood. Therefore, structural equation modeling was used to test theory-driven m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 93 publications
1
9
0
2
Order By: Relevance
“…51 The BDI data were treated as interval for the analyses. This is in line with previous studies, [45][46][47][48] and dichotomizing the data for logistic regression would incur a substantial loss of statistical power. 52,53 There is debate over the best way to conceptualize questionnaire data, 54 but we encourage attempts to replicate these findings using full-scale measures (eg, the Beck Scale for Suicidal Ideation 55 ).…”
Section: Limitationssupporting
confidence: 91%
See 1 more Smart Citation
“…51 The BDI data were treated as interval for the analyses. This is in line with previous studies, [45][46][47][48] and dichotomizing the data for logistic regression would incur a substantial loss of statistical power. 52,53 There is debate over the best way to conceptualize questionnaire data, 54 but we encourage attempts to replicate these findings using full-scale measures (eg, the Beck Scale for Suicidal Ideation 55 ).…”
Section: Limitationssupporting
confidence: 91%
“…44 All models were conducted with biascorrected confidence intervals based on 5000 samples. In line with previous studies, [45][46][47][48] suicidal ideation scores were treated as a continuous variable in all analyses.…”
Section: Negativementioning
confidence: 99%
“…The differential effects of childhood trauma subtypes reported here corroborate previous findings. Compared with other types of abuse, emotional abuse had the strongest associations with negative psychiatric outcomes (Barbosa et al ., 2014; de Araujo and Lara, 2016; Schmidt et al ., 2017), hypothalamic–adrenal–pituitary axis dysregulation (Braehler et al ., 2018) and suicidality (Anestis and Joiner, 2011; Schmidt et al ., 2017). It seems that emotional trauma amplifies the negative feelings of perceived burdensome and the lack of sense of belonging, more so than other types of adversities (Anestis and Joiner, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…‘The causal triangle’ between childhood trauma, cognitive biases and PLEs has been suggested in some theoretical accounts (Howes and Murray, 2014) and has recently been confirmed in independent studies (Gawęda et al ., 2018 a , 2018 b ; Gibson et al ., 2018). A recent study (Schmidt et al ., 2017) on ultra-high risk for psychosis patients showed that exposure to early life adversities is related to the risk of suicidality through cognitive disturbances and beliefs (e.g. negative self-concept and external attributions).…”
Section: Discussionmentioning
confidence: 99%